Genesis of the gneissic biotite granite in Lanhe, northern Guangdong: Constraints from zircon U–Pb geochronology, Hf isotopes, and geochemistry - WANG Haiyang; ZHONG Fujun; PAN Jiayong; XIA Fei; CHEN Zhengle; LI Wenli; LIU Jungang; SUN Yue; YAN Jie; QI Jiaming (Dizhi lixue xuebao, 2025)
Objective  The Lanhe pluton in northern Guangdong is located at the southeastern margin of the Zhuguangshan Complex and is primarily composed of gneissic biotite granite; its petrogenesis has not yet been determined.   Methods  This study applied LA–ICP–MS zircon U–Pb geochronology, whole-rock geochemistry, and zircon Hf isotope analyses to the Lanhe gneissic biotite granite.   Results  U–Pb dating indicates that the emplacement age of the Lanhe gneissic biotite granite is 427 ± 2 Ma, representing a product of the Caledonian magmatic activity. The geochemical characteristics show that the granite has SiO2 contents ranging from 71.53% to 75.41%, high total alkali contents (K2O + Na2O = 7.57%–8.23%), and high A/CNK values (1.00–1.06). It is enriched in Rb, Th, U, and K, but depleted in Ba, Y, Nb, Ta, Sr, and Yb. The LREE/HREE ratios range from 9.49 to 28.15, with significant Eu negative anomalies (δEu = 0.21–0.76). The zircon εHf(t) values of the samples are all negative (–11.8 to –5.2), with corresponding tDM2 values of 1806–2129 Ma.   Conclusion  Based on the geochemical and isotopic characteristics, the Lanhe gneissic biotite granite is identified as a highly fractionated I-type granite, primarily formed by partial melting of crustal metasedimentary rocks, including metagraywacke and metapelite. It is likely a product of the multi-stage reworking of the Paleoproterozoic basement during the Neoproterozoic to Early Paleozoic. The comprehensive study suggests that the Lanhe gneissic biotite granite formed in a syn-collisional tectonic setting during the Early Paleozoic in South China. [ Significance ] Integrated with the Zhuguang magmatic system and regional geological data, the Lanhe pluton likely represents a product of the transition from compressional thickening to post-collisional extension during the Caledonian Orogeny in South China. This transition may have been associated with intracontinental tectonic reorganization or external subduction–collision processes.